Implementasi Metode Muhadatsah Terhadap Keterampilan Berbicara Bahasa Arab Bagi Santri Pondok Pesantren Babus Salam Rajeg - Handi Wahyu Purnomo (GHAITSA : Islamic Education Journal, 2025)
This qualitative study investigates the effectiveness of the muhadatsah (conversation-based) method in improving Arabic speaking skills among students at Pondok Pesantren Babussalam Rajeg, utilizing in-depth interviews with two instructors. Findings demonstrate that structured conversational practice, including peer discussions (halaqoh) and impromptu speaking sessions, significantly enhances fluency, vocabulary retention, and communicative confidence by emphasizing active listening and speaking. However, challenges such as inconsistent teacher participation, heavy memorization loads, and limited informal practice opportunities hinder optimal outcomes. The study highlights the importance of a supportive linguistic environment, visual vocabulary aids, and peer motivation as key success factors, while recommending consistent methodological implementation and teacher training to address existing barriers. The results align with the sequential language acquisition model (listening → speaking → reading → writing), offering practical insights for enhancing Arabic pedagogy in Islamic boarding schools.